Numerical analysis of the heat extraction performance of mine backfill heat exchanger based on phase change heat storage (PCHS-BFHE) - Pai Ning; Feng Ju; Juan Xu; Meng Xiao; Tengfei Wang; Dong Wang; Lu Si (Case Studies in Thermal Engineering)
Deep mines contain a large amount of hot-rock geothermal energy, and one method to exploit it is to construct a backfill heat exchanger based on phase change heat storage (PCHS-BFHE) in the mine goaf. In this paper, the influence of the thermophysical parameters of phase change heat storage backfill (PCHSB), the heat extraction conditions, the groundwater seepage, and the heat exchange tube (HET) connection pattern on the heat extraction performance of PCHS-BFHE has been analyzed through numerical simulation, and a method for determining the reasonable tube spacing of the multi-tube series model has been proposed. The results indicate that the outlet-inlet temperature difference of the heat transfer fluid (HTF) is independent of the latent heat and the phase change temperature of PCHSB, but positively correlated with the thermal conductivity of PCHSB and the seepage velocity (perpendicular to the HET) of groundwater, negatively correlated with the inlet temperature and the mass flow rate of HTF. The multi-tube series model can obtain higher outlet temperature, but the total heat it extracts is lower. The proposed method for determining the reasonable tube spacing of the multi-tube series model is effective. The research results can provide theoretical support for the exploitation of mine geothermal.